(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
This study compared the predatory potential of nymphs of two dragonfly species viz. Crocothemis servilia (Drury, 1773) and Rhyothemis variegata (Linnaeus, 1763) using the different larval instars and pupae of Cx. quinquefasciatus (Say, 1823) as preys in normal laboratory settings. Field-collected fed and 24 h starved nymphs of C. servilia and R. variegata were offered 1st, 2nd, 3rd and 4th instar larvae and pupae of Cx. quinquefasciatus to monitor the rate of predation. A 24 h starved nymph of C. servilia showed the highest predation on the 2nd instar larvae (92.00±4.06%) followed by the 3rd (83.00±5.61%), 4th (80±6.89%) and 1st (76.00±4.85%) instar larvae and the pupae (26.00±2.91), respectively, whereas, that of R. variegata exhibited the highest consumption of the 1st instar larvae (90.00±3.54 %) followed by the 2nd (88.00±5.61 %), 3rd (82.00±3.74 %), 4th (70.00±7.91 %) larval instar and the pupae (23.00±4.63), respectively within 24 h exposure. In the same period, the fed nymphs of C. servilia showed maximum consumption of the 2nd instar larvae (77.00±3.54%) followed by the 3rd (76.00±4.58%), 4th (64.00±4.00%) and 1st instar (55.00±3.53%) larvae and the pupae (24.00±3.67), respectively, whereas, that of R. variegata exhibited highest consumption of the 1st instar larvae (67.00±5.38 %) followed by the 2nd (65.00±10.12 %), 3rd (58.00±8.46 %) and 4th (53.00±4.06 %) instar larvae and the pupae (21.00±2.92), respectively. The rate of predation was significant on all the larval instars and the pupae compared to their control counterparts (p<0.05) and the starved larvae and nymphs of both the dragonfly species showed higher predation compared to the fed nymphs. The aforementioned findings suggest that nymphs of both of the dragonfly species exhibited considerable predation potential against the immature stages of the Cx. quinquefasciatus mosquito. The present study recommends assessing the feasibility of using these species in large-scale mosquito control programs.